2017
DOI: 10.1016/j.jcot.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy of osteoarthritic patients after primary total knee arthroplasty

Abstract: These data suggest that patients undergoing TKA can expect similar life expectancy as the general population, with 66.6% of such patients surviving for at least 15-years. Additionally, patients undergoing bilateral TKAs may have a longer life expectancy than those undergoing unilateral TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, it was not a large cohort study. 20 Our study resulted in a lower mortality rate of patients after TKA up to a 12-year follow-up period, siding with the first group of studies. One previous study reported that younger patients aged <55 years had higher mortality and older patients aged >70 years had lower mortality rates than the general population up to 28-year follow-up.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, it was not a large cohort study. 20 Our study resulted in a lower mortality rate of patients after TKA up to a 12-year follow-up period, siding with the first group of studies. One previous study reported that younger patients aged <55 years had higher mortality and older patients aged >70 years had lower mortality rates than the general population up to 28-year follow-up.…”
Section: Discussionsupporting
confidence: 62%
“…There were some long-term studies regarding mortality after TKA, but they were not cohort studies. 20 Since we used data from HIRA, which include data from all citizens of Korea, we did not miss any participants due to follow-up loss. Therefore, the strength of this study lies in the results accurately representing the entire Korean population.…”
Section: Surgerymentioning
confidence: 99%
“…Therefore, greater volume did not decrease operative time. Considering Naranje et al’s findings, the surgeon’s skill in this study might have plateaued because he had already performed over 300 TKAs 7 years ago [ 26 ]. Therefore, it seems rational that the main reason explaining the shorter operative time over time was not increased surgeon’s skill but rather efficient instrumentation handoffs or delivery between the surgeon and the scrub nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the ratio of males to females was uneven. A female predominance of OA and TKA operations is a common finding of Asian patients [ 12 , 17 , 21 , 22 , 24 , 26 ]. Despite these limitations, the strength of this study was less surgeon-related bias than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, older age is related to higher mortality rates after total knee arthroplasty (TKA) among patients aged over 75 years [17] and after hip fracture surgery, with mortality rates for these patients observed to be over two times higher among men aged over 80 years than among men aged 65-69 years [18]. Notably, there are only 11 countries with a male life expectancy above 80 years, although this is more common for female life expectancy [1].…”
Section: Introductionmentioning
confidence: 99%